Forensic Accounting: Breaking the Nexus between Financial Cybercrime and Terrorist Financing in Nigeria - Olatunji Toyin Emmanuel; Aruwaji Akinola Michael (JAFFA, 2020)
This paper aims to examine forensic accounting (FA) investigation in tracking financial cybercrime (FC) and terrorist financing (TF) in Nigeria. It also verifies the associations between cyber criminality and terrorist financing. The sample composed of all Nigeria anti-graft agencies including the Nigeria Communication Commission (NCC). A quantitative method is used in a way to analyze the data. The results of the hypotheses revealed that forensic accounting has significant influence in disclosing the associations between financial cybercrime and terrorist financing. This study finds forensic accounting as a tool and deterrence to terrorist financing and associated crimes activities. The implications of this study emphasized that the government should strengthen enforcement on cybercrimes and provides security infrastructure (advanced technology) in tackling the precedence of financial cybercrime and terrorist financing in Nigeria.